2021
DOI: 10.1163/22134808-bja10064
|View full text |Cite
|
Sign up to set email alerts
|

Serial Dependence of Emotion Within and Between Stimulus Sensory Modalities

Abstract: How we perceive the world is not solely determined by what we sense at a given moment in time, but also by what we processed recently. Here we investigated whether such serial dependencies for emotional stimuli transfer from one modality to another. Participants were presented a random sequence of emotional sounds and images and instructed to rate the valence and arousal of each stimulus (Experiment 1). For both ratings, we conducted an intertrial analysis, based on whether the rating on the previous trial was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 65 publications
5
11
0
Order By: Relevance
“…We also observed feature tuning, which shows that participants' ratings for the current trial were influenced by the emotion of the previous trial only if the sequential emotions were similar. This finding supports previous research that has found only similar sequential emotions to be serially dependent ( Palumbo et al, 2017 ; Van der Burg et al, 2021 ). The result is also consistent with other studies that found serial dependence in the affect rating of emotional stimuli ( Palumbo et al, 2017 ; Van der Burg et al, 2021 ).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…We also observed feature tuning, which shows that participants' ratings for the current trial were influenced by the emotion of the previous trial only if the sequential emotions were similar. This finding supports previous research that has found only similar sequential emotions to be serially dependent ( Palumbo et al, 2017 ; Van der Burg et al, 2021 ). The result is also consistent with other studies that found serial dependence in the affect rating of emotional stimuli ( Palumbo et al, 2017 ; Van der Burg et al, 2021 ).…”
Section: Discussionsupporting
confidence: 92%
“…This finding supports previous research that has found only similar sequential emotions to be serially dependent ( Palumbo et al, 2017 ; Van der Burg et al, 2021 ). The result is also consistent with other studies that found serial dependence in the affect rating of emotional stimuli ( Palumbo et al, 2017 ; Van der Burg et al, 2021 ). Although many serial dependence studies use low-level stimuli in their investigation ( Kiyonaga et al, 2017 ), serial dependence has been found across many levels beyond just perception, including decision making ( Abrahamyan, Silva, Dakin, Carandini, & Gardner, 2016 ; Braun, Urai, & Donner, 2018 ; Fritsche, Mostert, & de Lange, 2017 ; Lueckmann, Macke, & Nienborg, 2018 ; Pascucci et al, 2019 ) and memory ( Barbosa et al, 2020 ; Kiyonaga et al, 2017 ).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations